Dinamika Pemanfaatan Pulut Balai Pada Adat Masyarakat Melayu di Desa Gunung Melayu Kabupaten Asahan Tahun 1980-Sekarang - Destia Luvita Sari; Laila Rohani; Franindya Purwaningtyas (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
In this case,the researcher discusses the use of Pulut Balai in every Malay traditional tradition in Asahan, the meaning of Pulut Balai, as well as the dynamics of changes in the form and meaning of Pulut Balai from 1980-present. This research uses an antropological approach, namely a way to understand a groupand human culture and their development. The method used to collect data in this research is a qualitative research method combining literature review and filed observation. The findings obtined from this research are, Pulut Balai is a continer for placing pulut used by the Malay community in various Malay traditions. Pulut Balai is a symbol of greatnes and the pride of the Malay tribe. Pulut Balai is used by the Malay community in Asahan for various tradition and has different meanings in each tradition. At the Upah-upah wedding and circumcision event, Pulut Balai is interpreted as a unification and hope for the family, at the Upah-upah Songgot Pulut Balai event it is interpreted as a symbol of the spirit and prayers of the person being singed, in the Pulut Balai Al-Qur'an Reading event, it is interpreted as a symbol of gratitude to Allah for the ability to read the Al-Qur'an, Meanwhile, the Upah-upah Berhaj/Umrah event means gratitude to Allah for the abundance of good fortune so that you can perform the Hajj or Umrah. However, as time progresses, Pulut Balai also experiences dynamics in form which influences its meaning. The Malay people pay less attention to the meaning elements of Pulut Balai, namely by modifying the appearance of Pulut Balai excessively, thus changing its appearance and meaning.